Anti-LAG-3 antibody LBL-007 plus anti-PD-1 antibody toripalimab in advanced nasopharyngeal carcinoma and other solid tumors: an open-label, multicenter, phase Ib/II trial - Chen, Gang; Sun, Dong-Chen; Ba, Yi; Zhang, Ya-Xiong; Zhou, Ting; Zhao, Yuan-Yuan; Zhao, Hong-Yun; Fang, Wen-Feng; Huang, Yan; Wang, Zhen; Deng, Chao; Hu, De-Sheng; et al. (Journal of hematology and oncology, 2025)
Open-label phase Ib/II study to investigate the safety and efficacy of LBL-007, an anti-LAG-3 antibody, plus toripalimab, an anti-PD-1 antibody, in patients with previously treated advanced nasopharyngeal carcinoma (NPC) and other solid tumors. Patients with advanced tumors refractory to prior standard therapies were enrolled. In phase Ib, patients received LBL-007 200 mg or 400 mg and toripalimab 240 mg intravenously once every 3 weeks. In phase II, all patients received LBL-007 at the recommended phase II dose (RP2D) and toripalimab 240 mg intravenously once every 3 weeks. The primary end points were safety in phase Ib and objective response rate (ORR) in phase II. The exploratory end point was the predictive capability of LAG-3 and PD-L1 expression for efficacy. Between November 30, 2021, and December 1, 2023, 80 patients were enrolled, including 30 (37.5%) with NPC and 50 (62.5%) with other tumors. Median follow-up was 26.0 months. In Phase Ib, LBL-007 was administered at 200 mg to four patients and 400 mg to six patients, with no dose-limiting toxicities observed. Therefore, the 400 mg dose of LBL-007 was established as the RP2D and administered to 70 patients in phase II. Nine (11.3%) of 80 patients had grade 3 or 4 treatment-related adverse events, the most common of which included anemia (2.5%), hyponatremia (2.5%), increased alanine aminotransferase (2.5%), increased aspartate aminotransferase (1.3%), and fatigue (1.3%). Eight patients (10.0%) had treatment-related serious adverse events. No treatment-related deaths were reported. In immunotherapy-naive NPC patients (n = 12), ORR was 33.3%, disease control rate (DCR) was 75%, and median progression-free survival (PFS) was 10.8 months (95% CI, 1.3 to not estimated). In IO-treated NPC patients (n = 17), ORR was 11.8%, DCR was 64.7%, and median PFS was 2.7 months (95% CI, 1.4 to 4.9). For other tumors, ORRs were 15.8% in immunotherapy-naive patients and 3.7% in immunotherapy-treated patients. Patients with ≥ 2 + LAG-3 expression had a higher ORR of 28.0%, compared to 7.7% in those with < 2 + LAG-3 expression. LBL-007 plus toripalimab exhibited a manageable safety profile in patients with advanced solid tumors and demonstrated promising antitumor activity in NPC, especially in immunotherapy-naive patients. These findings warrant further validation in future studies.